GREEN ACCOUNTING AND MANUFACTURING FIRM VALUE: ROLE OF FIRM SIZE - Annie Valentia; Alfonsus Jantong (Magister Akuntansi - Universitas Atma Jaya Makassar, 2026)
This study aims to investigate the role of firm size in the relationship between green accounting, environmental performance, and firm value. The study draws upon stakeholder theory and signaling theory. This study employs a purposive sampling method for sample selection. The population consists of all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period, totaling 241 companies. Based on the established criteria, 26 companies were selected, yielding a total of 78 data ready for processing. The analysis techniques used are multiple linear regression and moderated regression analysis. The results indicate that green accounting has a positive and significant effect on firm value, and environmental performance also has a positive and significant effect on firm value. However, firm size weakens the influence of both green accounting and environmental performance on firm value.